A Keyhole Review of the Large Paradigm Shift in Aortic Surgery: A Case Study of Thoracic Endovascular Aortic Repair (TEVAR) for Distal Aortic Arch Pseudoaneurysm in a Patient With Multiple Severe Underlying Medical Conditions - Wong, Matthew (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Open aortic surgery is well known to be associated with a high mortality rate, with up to 10% in elective setting and up to 30% in emergency setting. Since the advent of open aortic repair in the 1950s, we see the advancement of aortic surgical technique and technology – all for the sole purpose of improving the survival benefit of patient post surgery. Here we discuss a case study of utilizing the advancement of technology and knowledge in aortic repair in the form of Thoracic Endo Vascular Aortic Repair (TEVAR), in a complex case of a 69 years old patient with incidental finding of distal aortic arch pseudoaneurysm. His case was complicated with several debilitating medical conditions including left papillary renal cell carcinoma (RCC), toxic nodular goiter, and hypertension. This case study is a successful story of how far aortic surgical intervention has come along through the years - with smaller incision needed for the surgery, improvement in overall survival benefit, shorter hospital stay with early return to normal routine life, and making it a possibility to perform aortic repair surgery in a patient with multiple severe underlying medical conditions.